EFEITO ANESTÉSICO DO ÓLEO DE CRAVO EM JUVENIS DE PACU - SILVA, Wesley de Souza; OLIVEIRA, Fulvia Cristina; SILVA, Leonardo Augusto; OLIVEIRA, Evelyn Lopes; CAMPOS, Cristiane Meldau (ANAIS DO ENIC, 2017)
-